2012
DOI: 10.1186/1743-422x-9-155
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with recombinant enterovirus 71 viral capsid protein 1 fragment stimulated antibody responses in hamsters

Abstract: Enterovirus 71 (EV71) causes severe neurological diseases resulting in high mortality in young children worldwide. Development of an effective vaccine against EV71 infection is hampered by the lack of appropriate animal models for efficacy testing of candidate vaccines. Previously, we have successfully tested the immunogenicity and protectiveness of a candidate EV71 vaccine, containing recombinant Newcastle disease virus capsids that display an EV71 VP1 fragment (NPt-VP11-100) protein, in a mouse model of EV71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The reasons are not clear just as the reasons for a much higher incidence of complicated HFMD in children less than 5 years old are also not fully understood [ 7 ] but may due to immune system immaturity, relative availability of viral receptors or other unknown factors. In conclusion, we believe our orally-infected hamster is a good small animal model to further investigate viral pathogenesis, to model person-to-person transmission of EV-A71 infection, and to test the effectiveness of anti-viral drugs and vaccines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons are not clear just as the reasons for a much higher incidence of complicated HFMD in children less than 5 years old are also not fully understood [ 7 ] but may due to immune system immaturity, relative availability of viral receptors or other unknown factors. In conclusion, we believe our orally-infected hamster is a good small animal model to further investigate viral pathogenesis, to model person-to-person transmission of EV-A71 infection, and to test the effectiveness of anti-viral drugs and vaccines [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although infection by the natural oral route in animal models is desirable, it is rare and consistently successful infections have never been described [ 21 , 22 , 25 , 26 ]. Preliminary observations in a new hamster model used to test the protective efficacy of an EV-A71 candidate vaccine against infection by a mouse-adapted virus (MAV), suggested that it may be useful as an alternative small animal model for EV-A71 infection [ 27 ]. In this study, we report its further characterization as a suitable model for EV-A71 infection that could be consistently infected by the oral route.…”
Section: Introductionmentioning
confidence: 99%
“…Different delivery systems have been tested for their suitability in expressing the VP1 and to stimulate immune response. They include recombinant VP1 protein expressed in Escherichia coli BL21 [157] , recombinant Newcastle disease virus capsid displaying VP1 [171] , and VP1 expressed in yeast Pischia pastoris [172] . All induced high levels of neutralising antibodies.…”
Section: Subunit Vaccinementioning
confidence: 99%
“…In vitro / in vivo Safe to use Low immunogenicity [153,154,[163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178]…”
Section: Subunit Vaccineunclassified